2015
DOI: 10.1098/rspb.2015.0577
|View full text |Cite
|
Sign up to set email alerts
|

The role of ontogeny in physiological tolerance: decreasing hydrostatic pressure tolerance with development in the northern stone crabLithodes maja

Abstract: Extant deep-sea invertebrate fauna represent both ancient and recent invasions from shallow-water habitats. Hydrostatic pressure may present a significant physiological challenge to organisms seeking to colonize deeper waters or migrate ontogenetically. Pressure may be a key factor contributing to bottlenecks in the radiation of taxa and potentially drive speciation. Here, we assess shifts in the tolerance of hydrostatic pressure through early ontogeny of the northern stone crab Lithodes maja, which occupies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…This species is an established marine invertebrate research species for investigating hydrostatic pressure and temperature physiology, with several complementary studies conducted on it in recent years (Oliphant et al, 2011;Cottin et al, 2012;Ravaux et al, 2012). In addition, a recent study using the slope-depth king crab Lithodes maja showed comparable results at the gene expression level to previous responses observed in P. varians to elevated hydrostatic pressure, suggesting that P. varians can provide an insight into the responses of deeper-living species Munro et al, 2015). A temperature of 15°C was chosen as it is within the optimal temperature envelope of the species, and has been previously shown to be a level at which the sub-lethal effects of elevated pressure can be observed (Oliphant et al, 2011;Morris et al, 2015).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…This species is an established marine invertebrate research species for investigating hydrostatic pressure and temperature physiology, with several complementary studies conducted on it in recent years (Oliphant et al, 2011;Cottin et al, 2012;Ravaux et al, 2012). In addition, a recent study using the slope-depth king crab Lithodes maja showed comparable results at the gene expression level to previous responses observed in P. varians to elevated hydrostatic pressure, suggesting that P. varians can provide an insight into the responses of deeper-living species Munro et al, 2015). A temperature of 15°C was chosen as it is within the optimal temperature envelope of the species, and has been previously shown to be a level at which the sub-lethal effects of elevated pressure can be observed (Oliphant et al, 2011;Morris et al, 2015).…”
Section: Introductionsupporting
confidence: 58%
“…However, we believe that the mechanistic and experimental understanding gained from this study can provide a foundation from which longer-term, more ecologically relevant exposures can be conducted. Furthermore, a recent study conducted on a eurybaric king crab species, Lithodes maja, demonstrated comparable gene expression results at pressures outside its natural depth distribution limits (Munro et al, 2015). The comparability of these results suggests that the responses of the shallow-water shrimp P. varians can provide a valuable insight into the effects of pressure on deeper-living marine ectotherms.…”
Section: Discussionmentioning
confidence: 68%
“…The northern stone crab Lithodes maja (Linnaeus 1758) is distributed from 38°N along the North American coast to Newfoundland, across to the west and east coasts of Greenland, the coasts of Iceland, and down the Norwegian coast to the British Isles and the Netherlands, with a bathymetric distribution of 4-790 m (Zaklan, 2002;OBIS, 2016). Acute hyperbaric tolerance of L. maja's early development extends beyond the known bathymetric distribution of the species, but demonstrates an ontogenetic decrease that approaches the species' depth limit, suggesting that adult hyperbaric tolerance may influence bathymetric distribution in L. maja (Munro et al, 2015). Therefore, the aim of this study was to use L. maja as a model organism to determine: (1) mechanisms limiting hyperbaric tolerance, and (2) whether the adult critical hyperbaric threshold coincides with the species depth distribution limit.…”
Section: Introductionmentioning
confidence: 96%
“…Examining hyperbaric tolerance in the context of this framework offers the potential to identify the contribution of HP to bathymetric range limitation in marine organisms, and allow the fundamental effects of HP to be incorporated into the metabolic framework for ecology, which focuses on ecological effects on metabolic rate and consequent impacts on ecological processes at individual, population, community and ecosystem levels (Sibly et al, 2012). However, parameterising this model requires physiological data from sustained hyperbaric exposures at ecologically relevant temperatures in appropriate model taxa (Munro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At high concentrations, copper and cadmium reduce respiratory capacity, leading to a mismatch in oxygen supply and demand and ultimately resulting in death 49 70 . Hyperbaric neurophysiological stress at ecologically relevant temperatures appears to result from increased NMDA receptor activity in P. varians [40][41][42] , and also in the bathyal decapod Lithodes maja 68,71 .…”
Section: Mechanisms Of Toxicitymentioning
confidence: 98%